A Legal Analysis of Additional Fees on Payments Made Using QRIS in Indonesia - Maulana Ilham; Damayanti Samti Basar (CV. Publikasi Indonesia, 2026)
This study aims to analyze the implementation of QRIS (Quick Response Code Indonesian Standard) in Indonesia, focusing on the challenges faced in creating a fair and transparent payment system, and finding solutions to overcome these problems. This study also aims to explore merchant responsibilities and consumer protection in the use of QRIS, as well as the importance of consistent supervision and law enforcement. The research method used is descriptive-qualitative, with a literature study approach to examine various regulations related to QRIS, articles, and previous research on digital payment systems. This study identified several key challenges, such as lack of digital literacy, information asymmetry, and inconsistent supervision by authorities. In addition, this study also found that the disparity in digitalization between regions is an obstacle to the fair implementation of QRIS. The results show that to create a fair implementation of QRIS, it is necessary to increase education and outreach to merchants and consumers, strengthen supervision by Bank Indonesia, and utilize technology to accelerate law enforcement. With these steps, it is hoped that QRIS can be implemented more fairly and transparently, supporting financial inclusion in Indonesia.